A decomposition analysis of the emission of CO2 - Alex R. Hoen; Machiel Mulder (European Regional Science Association (ERSA), 2003)
In 1997 many countries, including the Netherlands, signed the Kyoto treaty. According to this protocol, the emission of CO2 in the Netherlands in the years 2008-2012 should be on average 6% below the level of 1990. However, the emission still shows an increasing pattern. Part of the increase may be compensated by supporting projects abroad, hence the goals may still be reached if domestic emission does not increase too far. All in all, it is not sure whether the Netherlands will meet the goals of this protocol. Several factors contribute to changes in the emission of CO2. The figures of CO2 emission only show the net effect. In order to see whether technological changes decreases the emission of CO2 and whether the increase in CO2 is mainly due to economic growth, this paper uses a decomposition analysis to compute the effect of these factors. In order not to complicate the analysis too much, it was decided to focus on the emissions of CO2 and ignore the other greenhouse gasses. The emission of CO2 is the most important issue, because CO2 is the most important greenhouse gas and because the emission of the other greenhouse gasses is decreasing whereas the emission of CO2 is increasing. Policy is therefore likely to be most effective if it focuses on CO2. Further, the decomposition method can only be used to analyse the emission of producers. Emission by consumers is therefore ignored.
Keywords: 330